2021
DOI: 10.3390/cells10113230
|View full text |Cite
|
Sign up to set email alerts
|

High Glucose Reduces the Paracellular Permeability of the Submandibular Gland Epithelium via the MiR-22-3p/Sp1/Claudin Pathway

Abstract: Tight junctions (TJs) play an important role in water, ion, and solute transport through the paracellular pathway of epithelial cells; however, their role in diabetes-induced salivary gland dysfunction remains unknown. Here, we found that the TJ proteins claudin-1 and claudin-3 were significantly increased in the submandibular glands (SMGs) of db/db mice and high glucose (HG)-treated human SMGs. HG decreased paracellular permeability and increased claudin-1 and claudin-3 expression in SMG-C6 cells. Knockdown o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 51 publications
1
5
0
Order By: Relevance
“…In the current study, compared to the Control rats, the DM rats show decreased intestinal barrier function, as demonstrated by decreased gene and protein (colon) expression of Claudin-3. Our findings are consistent with the previous studies using HFD-induced prediabetic mice [ 22 ] and db/db diabetic mice [ 23 , 24 ]. Nascimento et al reported that the tight junction-mediated barrier in intestinal tissues, such as the duodenum, jejunum, ileum and colon epithelia, was significantly weakened in prediabetic mice [ 22 ].…”
Section: Discussionsupporting
confidence: 94%
“…In the current study, compared to the Control rats, the DM rats show decreased intestinal barrier function, as demonstrated by decreased gene and protein (colon) expression of Claudin-3. Our findings are consistent with the previous studies using HFD-induced prediabetic mice [ 22 ] and db/db diabetic mice [ 23 , 24 ]. Nascimento et al reported that the tight junction-mediated barrier in intestinal tissues, such as the duodenum, jejunum, ileum and colon epithelia, was significantly weakened in prediabetic mice [ 22 ].…”
Section: Discussionsupporting
confidence: 94%
“…There were 2 transcripts relative to actin and 4 transcripts relative to tubulin changing significantly in the aortas of Angiotensin II‐infused mice (Table S5). For diabetes mellitus, streptozotocin injected mice (GSE179718 [39], GSE179717 [39], and GSE155377), diabetes‐prone db/db mice (GSE169275 [40] and GSE141411 [41]), and diabetes‐resistant ob/ob mice (GSE169275 [39]) were analyzed. As a result, 1 transcript about actin and 1 transcript about tubulin changed significantly in visceral adipose tissue of streptozotocin‐injected mice.…”
Section: Resultsmentioning
confidence: 99%
“…The expression and mitochondrial fission of SP1 was found to be significantly increased in a diabetic or high-glucose environment [ 38 ]. Similarly, elevated SP1 level was detected in diabetic submandibular glands as well as the high-glucose-treated SMG-C6 cells, which was induced by the downregulation of its suppressor microRNA-22-3p [ 39 ]. As a transcription factor, SP1 bound to the promoter of phosphoglycerate mutase family member 5 to aggravate diabetic renal tubular injury [ 38 ].…”
Section: Discussionmentioning
confidence: 99%